Modeling absorption spectra of molecules in solution. Issue 1 (13th September 2018) - Zuehlsdorff, Tim J.; Isborn, Christine M.
Abstract : The presence of solvent tunes many properties of a molecule, such as its ground and excited state geometry, dipole moment, excitation energy, and absorption spectrum. Because the energy of the system will vary depending on the solvent configuration, explicit solute–solvent interactions are key to understanding solution‐phase reactivity and spectroscopy, simulating accurate inhomogeneous broadening, and predicting absorption spectra. In this tutorial review, we give an overview of factors to consider when modeling excited states of molecules interacting with explicit solvent. We provide practical guidelines for sampling solute–solvent configurations, choosing a solvent model, performing the excited state electronic structure calculations, and computing spectral lineshapes. We also present our recent results combining the vertical excitation energies computed from an ensemble of solute–solvent configurations with the vibronic spectra obtained from a small number of frozen solvent configurations, resulting in improved simulation of absorption spectra for molecules in solution. Abstract : In this tutorial review, an overview is given of factors to consider when modeling excited states of molecules interacting with explicit solvent. Guidelines are provided for sampling solute‐solvent congurations, choosing a solvent model, performing the excited state electronic structure calculations, and computing spectral lineshapes. Recent results are presented for combining the vertical excitation energies computed from an ensemble of solute‐solvent congurations with vibronic eects, resulting in improved simulation of lineshapes for molecules in solution.